Binary collisions of dark matter blobs - Melissa D. Diamond; David E. Kaplan; Surjeet Rajendran (Journal of High Energy Physics, 2023)
Abstract We describe the model-independent mechanism by which dark matter and dark matter structures heavier than ~ 8 × 1011 GeV form binary pairs in the early Universe that spin down and merge both in the present and throughout the Universe’s history, producing potentially observable signals. Sufficiently dense dark objects will dominantly collide through binary mergers instead of random collisions. We detail how one would estimate the merger rate accounting for finite size effects, multibody interactions, and friction with the thermal bath. We predict how mergers of dark dense objects could be detected through gravitational and electromagnetic signals, noting that such mergers could be a unique source of high frequency gravitational waves. We rule out objects whose presence would contradict observations of the CMB and diffuse gamma-rays.